A Biofuel Cell Based on Biocatalytic Reactions of Glucose on Both Anode and Cathode Electrodes. Issue 4 (21st December 2016) - Koushanpour, Ashkan; Gamella, Maria; Guz, Nataliia; Katz, Evgeny
Abstract: Biofuel cells based on electrocatalytic oxidation of NADH and reduction of H2 O2 have been prepared using carbon fiber electrodes functionalized with graphene nano‐flakes. The electrochemical oxidation of NADH was catalyzed by Meldola's blue (MB), while the reduction of H2 O2 was catalyzed by hemin, both catalysts were adsorbed on the graphene flakes due to their π‐π staking. In the next set of experiments, the MB‐ and hemin‐electrodes were additionally modified with glucose dehydrogenase (GDH) and glucose oxidase (GOx), respectively. The enzyme catalyzed reactions in the presence of glucose, NAD + and O2 resulted in the production of NADH and H2 O2 in situ. The produced NADH and H2 O2 were oxidized and reduced, respectively, at the bioelectrocatalytic electrodes, thus producing voltage and current generated by the biofuel cell. The enzyme‐based biofuel cells operated in a human serum solution modelling an implantable device powered from the natural biofluid. Finally, two enzyme‐based biofuel cell connected in series and operating in the serum solution produced electrical power sufficient for activation of an electronic watch used as an example device. Abstract :